Kalapani and the changing contours of India–Nepal relations - Bhutia, Lhamu Tshering (A Bi-annual South Asian Journal of Research & Innovation, 2025)
India and Nepal share a historically deep and multidimensional relationship, reinforced by cultural, religious, and geographic linkages, as well as an open border under the 1950 Treaty of Peace and Friendship. While fostering integration and interdependence, structural asymmetries have fueled periodic tensions, with the Kalapani dispute emerging as a symbol of contested sovereignty and shifting strategic dynamics. In this context, the Kalapani territorial dispute has evolved into a potent symbol of contested sovereignty and national identity, exposing the deeper structural issues in an otherwise interdependent relationship and signalling a shift in the strategic calculus of India-Nepal bilateralism. By situating Kalapani within the larger framework of India’s evolving border relations, this article examines the historical roots, geopolitical significance, and regional implications of the Kalapani dispute, emphasising that border disputes profoundly shape bilateral trust and narratives. The study highlights the dual importance of Kalapani as both a site of strategic control over vital Himalayan passes and as a potent symbol in the politics of sovereignty and nationalism. The study further underscores the imperative of sustained diplomacy and institutionalised cooperation to resolve the issue and strengthen stability along the Himalayan frontier.